Improving Students’ Achievement on Reading Comprehension through Before, During, and After (BDA) TechniqueThe objective of this study is to investigate whether the application of Before, During, and After (BDA) Technique - Misbahudin Misbahudin; Tjut Ernidawati (Universitas Negeri Medan, 2012)
The objective of this study is to investigate whether the application of Before, During, and After (BDA) Technique significantly improves the students’ achievement in reading narrative text. This study was conducted by using classroom action research. The subject of this research was the students in MTs S Al-Ittihadiyah Mamiyai Medan especially class VIII 1 which consisted of 32 students. The research was conducted in two cycles. The first cycle consisted of three meetings and the second cycle consisted of three meetings. The instruments for collecting data were interview sheet, observation sheet, and diary notes. Based on the analysis, students’ achievement is improved in every test of reading narrative test. In test I, the mean score was 50.93. In test II in cycle I, the mean score was 70.93. In test III in cycle II, the mean score was 91.75. Based on the interview sheet, observation sheet and diary notes, it was found that the teaching learning process ran well. The students were more active and enthusiastic working in group. It was conclude that Before, During, and After (BDA) Technique can improve the students’ achievement in reading narrative text. Keywords: BDA Technique, Reading, Narrative text, Action Research